A Study on the Effect of Emotional Intelligence on Occupational Stress of Teachers – With Special Reference to Teachers in Kottayam District: Exploring the Impact of Emotional Intelligence on Occupational Stress among Teachers in Kottayam District (Journal of Advances and Scholarly Researches in Allied Education, 2017)
True education is beyond earning degrees. It is more than bookish knowledge. Education means inculcating moral values, positive thinking, attitude of helping, attitude of giving to society and ethical values. Students educated this way are able to bring changes in society. Because of tremendous changes in Educational sector today, teacher is expected to possess a multifaceted personality. Their work place now is a high stressed environment. This is sure to affect their effectiveness in teaching. In order to cope with such type of problems, teachers and principals need to possess additional competencies such as Emotional Intelligence. The main assumption of the research has been proved according to the relationship between emotional intelligence and occupational stress and shows that by increasing the emotional intelligence can reduce the occupational stress of employees and improve their work.